PENGARUH INTEGRASI MODEL LEARNING CYCLE 5E DAN MEDIA AUGMENTED REALITY (AR) TERHADAP HASIL BELAJAR EKONOMI SISWA SMA - crusma fradani, ayis (UIR PRESS, 2025)
This study aims to analyze the effect of integrating the Learning Cycle 5E instructional model with Augmented Reality (AR) media on high school students’ economics learning outcomes. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all eleventh-grade students at SMA Negeri 1 Kedungadem, Bojonegoro, with class XI-8 (36 students) designated as the experimental group and class XI-7 (36 students) as the control group. The research instrument was a learning achievement test comprising 20 multiple choice items that had been tested for validity, reliability, difficulty level, and discrimination index. The findings revealed that the experimental group achieved an average score of 82.4, while the control group obtained an average score of 71.2. A paired sample t-test produced a t-value of 6.87, which exceeded the critical t-table value of 2.03 (α = 0.05). This result indicates a significant effect of integrating the Learning Cycle 5E model with Augmented Reality (AR) on students’ economics learning outcomes. The findings support constructivist theory, which emphasizes the importance of active and contextual learning experiences. Theoretically, this study extends the examination of the effectiveness of the Learning Cycle 5E model by incorporating immersive technology, namely Augmented Reality (AR). Practically, the results provide recommendations for economics teachers to utilize Augmented Reality (AR) technology in creating more interactive, engaging, and relevant learning experiences that meet the needs of the digital generation.